Agave americana 'Marginata' Variegated Century Plant - Edward Gilman; Ryan W. Klein; Gail Hansen (EDIS)
This document is about the variegated century plant (Agave americana ‘Marginata’), detailing its characteristics, cultivation, and uses. It describes the plant’s distinctive appearance with twisted green leaves and bright yellow margins, and its hardy nature, tolerating heat, drought, and salty conditions. The document also covers planting guidelines, including its preferred USDA hardiness zones, soil tolerances, and spacing requirements. Additionally, it highlights the ornamental value of the plant, suggesting companion plants to enhance its visual appeal in landscapes.